2018
DOI: 10.1186/s12905-018-0510-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of cervical cancer and HPV vaccine in Bangladeshi women: a population based, cross-sectional study

Abstract: BackgroundThe objective of this study was to assess the level of knowledge of cervical cancer among Bangladeshi women and to assess their willingness to receive the human papillomavirus (HPV) vaccine.MethodsA population-based, cross-sectional survey was conducted from July to December 2011 in one urban and one rural area of Bangladesh. A total of 2037 ever-married women, aged 14 to 64 years, were interviewed using a structured questionnaire. Data on socio-demographic characteristics and knowledge of cervical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 34 publications
10
46
0
Order By: Relevance
“…In early 2018, data using a cross-sectional study of Bangladeshi women with low educational attainment (mean: ∼7 years of education) and low income showed, despite poor knowledge of cervical cancer, willingness to obtain HPV vaccination was very high. 18 One other previous report of Bangladeshi women has documented high (81%) awareness of cervical cancer, however, the majority (74%) of these data were collected from women residing in rural areas and limited to women above the age of 30 years; however, this study found high awareness, but did not explore willingness to vaccinate oneself or their daughters. 19 On the contrary, in another African study, 20 low awareness was related to increased willingness to vaccinate one's child, but not oneself.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…In early 2018, data using a cross-sectional study of Bangladeshi women with low educational attainment (mean: ∼7 years of education) and low income showed, despite poor knowledge of cervical cancer, willingness to obtain HPV vaccination was very high. 18 One other previous report of Bangladeshi women has documented high (81%) awareness of cervical cancer, however, the majority (74%) of these data were collected from women residing in rural areas and limited to women above the age of 30 years; however, this study found high awareness, but did not explore willingness to vaccinate oneself or their daughters. 19 On the contrary, in another African study, 20 low awareness was related to increased willingness to vaccinate one's child, but not oneself.…”
Section: Introductionmentioning
confidence: 67%
“…Previous studies conducted in Bangladesh identified the importance of neighbors and relatives as a source of knowledge of cervical cancer, indicating that social network is an important source of knowledge. 18 Involving men in educational efforts would improve the social acceptance of discussing HPV and cervical cancer, which may be vital to efforts in the future to vaccinate young boys in Bangladesh. Such efforts have been previously reported to be an effective and important public health strategy for HPV vaccination program success and effective uptake of vaccination among both adolescent girls and boys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding people's knowledge and attitude towards HPV infection and vaccination may facilitate to design of effective strategies and interventions in raising awareness and encouraging the uptake of the vaccine among the target population. Previous studies on knowledge and attitudes towards HPV infection and vaccination has focused on women in Bangladesh 11,12 . However, there is a lack of research that explores young adult's knowledge and attitude towards HPV infection and vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Chi-Square test which is normally known as independence test is used to test the hypotheses for categorical variables and to test whether these variables are independent population variable. Chi-Square test can be calculated by finding the summation of dividing the square difference between the observed (O) and the expected (E) values by the expected value for each category in data as shown in Formula 1 12 .…”
Section: Methodsmentioning
confidence: 99%